Legal Integration of Customary Law within Indonesia’s National Land Law System - Lubis, Ikhsan; Lubis, Duma Indah Sari Lubis; Lubis, Andi Hakim Lubis (Jurnal Mulawarman Law Review, 2025)
This article examines the legal integration of customary law into Indonesia’s national land law system, with specific reference to the constitutional framework and the Basic Agrarian Law. The purpose of this study is to analyze the status of customary law, identify its impacts on land tenure and use, and formulate legal strategies to harmonize customary and national law toward equitable and sustainable land governance. Employing a normative juridical method, the research draws on primary legal materials, including statutory regulations, constitutional provisions, and jurisprudence, supported by secondary academic sources. The findings indicate that although customary law is constitutionally recognized, its implementation remains inconsistent due to legal fragmentation, administrative constraints, and sectoral regulatory conflicts. To address this, the study proposes a pluralistic legal model based on codification, procedural innovation, institutional reform, and participatory law-making to ensure the effective and just integration of customary land systems within the national legal order.